EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE PAIRS CHECK (PC), THINK PAIR SHARE (TPS), DAN PROBLEM BASED LEARNING (PBL) PADA MATERI KUBUS DAN BALOK DITINJAU DARI GAYA BELAJAR SISWA KELAS VIII SMP NEGERI SE-KOTA SURAKARTA - Suci Irawati; Budiyono Budiyono; Isnandar Slamet (Jurnal Pembelajaran Matematika, 2015)
Abstract: This study aimed at determining the effect of learning models on the learning achievement in Mathematics viewed from the students’ Learning Style. The learning models compared were learning model Pairs Check (PC), Think Pair Share (TPS) and Problem Based Learning (PBL). This research was a quasi-experimental research with 3×3 factorial design. The population of research was all grade VIII students of Junior High School (SMP) in Surakarta. The samples were chosen by using stratified cluster random sampling. The instruments used were achievement test and questionnaire of learning styles. The technique of analyzing the data was two-ways ANOVA with unbalanced cells. The results of research showed as follows. (1) The PC resulted better learning achievement than the TPS and PBL. TPS resulted learning achievement as good as PBL, (2) The students having visual learning style resulted better learning achievement than did those having auditorial learning style. The students having visual learning style resulted better learning achievement than those having kinesthetic learning style. The students having auditorial learning style resulted better learning achievement than those having kinesthetic learning style. (3) At the students having visual learning style, PC resulted better learning achievement than that TPS and PBL, TPS and PBL resulted the same learning achievement. At the students having auditorial learning style, PC and TPS resulted the same learning achievement, PC resulted better learning achievement than that PBL, TPS resulted better learning achievement than that PBL. At the students having auditorial learning style, PC, TPS and PBL resulted the same learning achievement, (4) In PC, the students having visual learning style resulted learning achievement as good as those having auditorial learning style, the students having visual learning style resulted better learning achievement than did those having auditorial learning style, The students having auditorial learning style resulted learning achievement as good as those having kinestetik learning style. In TPS and PBL, The students having visual learning style resulted learning achievement as good as those having auditorial and kinestetik learning style.Keywords : Pairs Check (PC), Think Pair Share (TPS), Problem Based Learning (PBL), Learning Style.